Effect of pH and salinity on filtration rate of angelwing clam. Pholas orientalis (Gmelin, 1790) - Ta-aca, Grace Salve (2015.)
Ingestion rate (IR) of mature angelwing clam, Pholas orientalis (80-100mm) was studied at various lebels of pH and salinity. The pH treatment were 6.6-6.7; 7.0-7.1; 7.4-7.5; and 7.8-7.9. The salinity treatments were 15, 20, 25 and 30 ppt. The clams were fed with Tetraselmis sp. at a concentration of -160,000 cells ml-1 for the pH experiment and -300,000 cells ml-1 for the salinity wxperiment. This was followed by pH of 7.0-7.1; then by pH of 7.4-7.5; and lowest at ph of differences in the IR among pH of 6.6-6.7, 7.0-7.1; and 7.4-7.5. For the salinity experiment, IR was the highest at 30ppt. This was followed by 25, 20 and 15ppt, respectively. One-way ANOVA, however, did not show differences among the different salinity treatments.
Special Problem (Undergraduate, Bachelor of Science in Biology. University of the Philippines Visayas, Miagao, Iloilo
Keywords: Angelwing Clam, Pholas orientalis (Gmelin 1790); Filtration